1125. Reduced Time to Pathogen Identification and Antibiotic Prescription Using Multiplex Molecular Testing for Gastrointestinal Infections. (26th November 2018) - Kardasheva, Aleksandra; Yount, Evan; Rose, Tracie; Verma, Punam; Chihara, Shingo
Abstract: Background: A variety of microbial pathogens causes diarrhea which remains a significant global concern. The ability to rapidly identify the pathogen impacts the decision to treat, promotes antimicrobial stewardship, and assists with infection control and prevention. The objective of the study was to compare the time it took for rapid identification of microbial pathogens via a stool-culture based testing vs. real-time PCR using a Verigene Enteric Pathogens (EP) test. Methods: The study was performed at Virginia Mason Medical Center, a tertiary medical center in Seattle. A retrospective chart review included the diagnosis of microbial pathogen, antibiotics prescribed (if any), time of prescription, duration of antibiotics course and patients' outcome if they were hospitalized. Stool specimens from 136 patients in 2015 were analyzed via a stool-culture based method. The results were compared with a molecular-based method used to study specimens from 225 patients in 2017. Years 2015 and 2017 were chosen as in 2016 the culture-dependent testing was replaced by culture independent. T-test was used to examine the difference in time to identification of the pathogen and time to prescription between 2015 and 2017. SAS 9.4 was used for the analysis. Results: In 2015, 2, 194 stool specimens were tested and 136 (6.2%) were positive. In 2017, 2, 037 stool specimens were examined and 225 (11%) returned positive. The median time to prescription in 2015 was 53.84 hours in comparison to 21.96 hours in 2017 ( P < 0.0001). The time to identification of the pathogen was 60.05 hours in 2015 vs. 22.53 hours in 2017 ( P < 0.0001). The TAT (turnaround time), defined as the time from the specimen being received in the laboratory to the finalized result, was 167.92 hours vs. 156.35 hours, respectively ( P = 0.75). Conclusion: Multiplex PCR assays for enteric pathogens showed higher sensitivity when compared with standard culture-based methods. When the clinician felt antibiotics were indicated, there was a significantly shorter time to antibiotics prescription. Aside from a shorter time to microbial identification, molecular assays detect an increased number of pathogens from a single specimen that has an important impact on infection prevention and appropriate treatment. Disclosures: All authors: No reported disclosures.